The influence of body weight of patients with chronic plaque psoriasis on biological treatment response - Kisielnicka, Anna; Szczerkowska-Dobosz, Aneta; Nowicki, Roman (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Psoriasis is a chronic inflammatory disease of the skin. The new era of biological therapies initiated a shift in the definition of the disease therapeutic success, however, recent reports in the literature draw attention to the treatment-induced weight gain in psoriatic patients. Therefore, it is worth considering the body mass index influence on the biological treatment of chronic plaque psoriasis, seeing that it has manifold associations with the disease and may play an important role in clinical practice management.